Siri Polygamy from the Perspective of Islamic Law Versus State Law: A Study of Sociology and Legal Pluralism - Ainun Yasminnatul Mu’minah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines siri polygamy in Indonesia through the analytical lens of sociology and legal pluralism by exploring the interaction between Islamic law and state law in the construction of marital legitimacy and dispute resolution. The research employs a non empirical legal method based on normative legal analysis and a socio legal approach. Data were derived from constitutional provisions, marriage legislation, the Compilation of Islamic Law, judicial decisions, and relevant academic literature. The findings indicate that siri polygamy operates within a field of competing normative authorities where religious validity may coexist with limited state recognition. This condition generates legal uncertainty concerning marital status, child protection, inheritance rights, and access to justice. Judicial practice demonstrates a tendency to accommodate social realities through legalization mechanisms rather than relying exclusively on criminal sanctions. The study further reveals that women and children remain the most vulnerable parties within unregistered polygamous relationships. From a criminal law policy perspective, effective regulation requires a balanced approach that integrates legal certainty, substantive justice, and social legitimacy. The research argues that harmonization between Islamic family law and national law is essential for strengthening rights protection and improving the coherence of Indonesia’s plural legal system.